Comportamientos de riesgo adolescente : una aproximación psicosocial - Peñaherrera Sánchez, Edwin (1998)
This study discusses the traditional way of understanding behavioral risk at adolescence, proposing a psychosocial perspective of the concept of risk. It is known that the biomedical approach of health is centered in consequences and damage, but adolescence health and risk are related with a complex web of causation that acts before the risk involvement, supporting it. This study shows that it is necessary to analyze not only the behavioral consequences bur the antecedents and the function that these behaviors have in their lives and in solve the developmental tasks present in each society. Then it will be possible to design appropriate and effective prevention programs.